Children's safety behaviour at School - Rofiatun, Rofiatun; Julaikah, Julaikah; Tirsilowati, Sri Yuni (Riset Informasi Kesehatan, 2025)
Background: Cognitive limitations and low understanding of the dangers around them make them less able to anticipate and overcome these dangers. Places that have the potential to cause accidents in children can come from anywhere, be it the highway, home and its surroundings, school and its surroundings. Accidents at school are the cause of 40% of injuries in children. Lack of understanding of risks or dangers, use of unsafe equipment, and the materials used also affect children's safety. This study aims to determine the determinants of safety behavior in children in elementary schools. Method: This research used mixed methods and Convergent Parallel Design approaches.. Researchers collected quantitative data for the safety knowledge variable, while qualitative data for safety perceptions, safety behavior and availability of safety infrastructure. The research subjects were students and teachers, at SD Muhammdiyah Guntur Geni Srandakan District. Statistical test analysis using the Chi Square Test and logistic regression test for quantitative data. Result : there were 65.57% of respondents who had good knowledge and 75.41% of respondents had good safety behaviour. 44% of safety infrastructure is available in schools. 40 or 66% of respondents had a history of accidents at school such as falls, scratches and sprains. Conclusion: Students who have good knowledge are 1.7 times more likely to have good safety behavior.